(5y-6)*(4-y)=0

Simple and best practice solution for (5y-6)*(4-y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5y-6)*(4-y)=0 equation:



(5y-6)(4-y)=0
We add all the numbers together, and all the variables
(5y-6)(-1y+4)=0
We multiply parentheses ..
(-5y^2+20y+6y-24)=0
We get rid of parentheses
-5y^2+20y+6y-24=0
We add all the numbers together, and all the variables
-5y^2+26y-24=0
a = -5; b = 26; c = -24;
Δ = b2-4ac
Δ = 262-4·(-5)·(-24)
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{196}=14$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(26)-14}{2*-5}=\frac{-40}{-10} =+4 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(26)+14}{2*-5}=\frac{-12}{-10} =1+1/5 $

See similar equations:

| 8y^2-12y-6=8 | | (7-u)(5u+1)=0 | | 2x/2=6 | | 33+x=50 | | x=3=-x-5 | | 4+n=-9+(-9) | | ×=5=y=6 | | |2x-3|=-5 | | y=15–3yy+13+y | | 56+4x=16 | | 8x−67+8x-75=180 | | 2x2+5x=-3 | | 10x2-48x+32=0 | | 9/11=x7 | | 11/9=7x | | 10k2-7k-12=0 | | 4^9x=5^x-8 | | X=88+-1y | | 3(v-9)=7v+5 | | 0.2x+0.4(5)=0.3(x+2)= | | (c−2)/10=7 | | 3^x1=12 | | 3/5g-1/3=-11/3 | | 1=8-3x^2 | | -6(7f-5)=22-3f | | 6+12n-2=7n+44-5n | | (2-m)/6=1 | | 8y+7+6y=-28 | | 2a^2-54=a^2+27 | | 3x-1+3x+1=90 | | (2-m)/6=6 | | -24=-3(5c-7) |

Equations solver categories